Point-of-care testing diagnosis of African swine fever virus by targeting multiple genes with enzymatic recombinase amplification and CRISPR/Cas12a System - Cao, Shinuo; Ma, Dongxue; Xie, Jun; Wu, Zhi; Yan, Haoyu; Ji, Shengwei; Zhou, Mo; Zhu, Shanyuan (Frontiers in Cellular and Infection Microbiology, 2024)
African swine fever virus (ASFV) infection is causing devastating outbreaks globally; pig farming has suffered severe economic losses due to the ASFV. Currently, strict biosecurity control measures can mitigate the incidence of ASF. Rapid, cost-effective, and sensitive detection of ASFV can significantly reduce disease transmission and mortality. CRISPR/Cas-associated proteins can detect polymorphisms with high specificity and sensitivity, making them ideal for detecting pathogens. In this study, based on CRISPR/Cas12a integrated with enzymatic recombinase amplification (ERA) technology, a CRISPR/Cas12a detection system capable of identifying ASFV E183L, K205R, and C962R gene sequences has been developed. The ERA-CRISPR/Cas12a detection system detected ASFV precisely without cross-reactivity with other porcine pathogen templates and with a sensitivity detection limit of 10 copies per reaction; it takes 60 minutes to complete the detection process. In combination with this integrated ERA pre-amplification and Cas12a/crRNA cutting assay, it provides a rapid, straightforward, sensitive, and specific method for ASFV detection in the field.